Environmental Quality Assessment of Planned Residential Areas in a Peri-Urban Zone Under Urban Sprawl Pressure: A Case Study of Ingin Jaya Subdistrict, Indonesia - Hasan, Zainuddin; Arisaputri, Sri Batara Nurfajri; Alicia, Fradisa; Sabila, Farisa; Fuady, Zahrul (Elkawnie, 2025)
Abstract: Urban sprawl in peri-urban areas encourages rapid growth of planned settlements, but this is often not accompanied by the provision of adequate basic infrastructure, thereby potentially reducing the quality of the settlement environment. This study aims to quantitatively assess the quality of planned settlements in Ingin Jaya Subdistrict, Aceh Besar Regency, as a peri-urban area experiencing post-disaster urban sprawl pressure. The assessment was conducted at the residential block level using a scoring and weighting method based on seven environmental quality parameters, including building layout, width and condition of access roads, residential location, drainage system, availability of clean water, and waste management facilities. A total of 61 residential blocks were analyzed out of 286 blocks, using proportional stratified random sampling. The results of the study show that 52% of residential blocks are in good condition, 36% are in fair condition, and 12% are in poor condition. The parameters of building layout and clean water availability generally meet the standards, while road width, road condition, drainage systems, and waste management facilities are the main factors causing a decline in the environmental quality of residential areas. Based on these evaluation results, improvement guidelines were formulated, focusing on enhancing basic infrastructure, enforcing spatial planning regulations, and strengthening the roles of local governments, developers, and the community. Abstrak: Urban sprawl di kawasan peri-urban mendorong pertumbuhan pesat permukiman terencana, namun perkembangan tersebut sering kali tidak diikuti oleh penyediaan infrastruktur dasar yang memadai, sehingga berpotensi menurunkan kualitas lingkungan permukiman. Penelitian ini bertujuan untuk menilai secara kuantitatif kualitas lingkungan permukiman terencana di Kecamatan Ingin Jaya, Kabupaten Aceh Besar, sebagai kawasan peri-urban yang mengalami tekanan urban sprawl pascabencana. Penilaian dilakukan pada tingkat blok permukiman dengan menggunakan metode skoring dan pembobotan berdasarkan tujuh parameter kualitas lingkungan, meliputi tata letak bangunan, lebar dan kondisi jalan masuk, lokasi permukiman, sistem drainase, ketersediaan air bersih, serta fasilitas pengelolaan sampah. Sebanyak 61 blok permukiman dianalisis dari total 286 blok melalui teknik proportional stratified random sampling. Hasil penelitian menunjukkan bahwa 52% blok permukiman berada pada kategori baik, 36% kategori sedang, dan 12% kategori buruk. Parameter tata letak bangunan dan ketersediaan air bersih umumnya telah memenuhi standar, sementara lebar jalan masuk, kondisi permukaan jalan, sistem drainase, dan fasilitas persampahan menjadi faktor utama yang menyebabkan penurunan kualitas lingkungan permukiman. Berdasarkan hasil evaluasi tersebut, dirumuskan arahan peningkatan kualitas permukiman yang bersifat empiris, dengan penekanan pada perbaikan infrastruktur dasar, penegakan pengendalian pemanfaatan ruang, serta penguatan peran pemerintah daerah, pengembang, dan masyarakat dalam pengelolaan permukiman secara berkelanjutan.